WHY BACKRONYMS? INVESTIGATING STRATEGIC LANGUAGE PLAY IN @BIASALAHANAKMUDA - Ririn Susetyaningsih; Suhandano (Acceleration: Multidisciplinary Research Journal, 2026)
This study investigates the motives of using backronyms in the Indonesian Instagram discourse, focusing on the account @biasalahanakmuda, related to the backronyms’ communicative functions in social media interaction. The data consists of 137 backronymic items with 189 occurrences, collected from Instagram posts, captions, and stories posted between July 10, 2020 and April 27, 2026. The data were selected using purposive sampling based on three criteria: (1) the item is an existing lexical form or acronym-like expression, (2) a new invented expansion was assigned to it, and (3) the expansion resulted in a different meaning than the original form. This research employed a qualitative descriptive method supported by quantitative calculation. The analytical approach combined morphological analysis, especially Kridalaksana’s rules of acronym formation, with pragmatic and digital discourse analysis to examine how the backronyms are structurally formed and communicatively used in Instagram discourse.  Each backronymic item was interpreted in relation to its original form, its invented expansion, its Instagram context, and its pragmatic function. Data validity was enhanced by contextual verification with the aid of screenshots, and systematic coding ensured the reliability of analysis. The results show that backronyms are used for four general reasons: entertainment, audience engagement and group intimacy, evaluation and criticism, and identity and stance marking. Findings suggest that backronyms are not merely playful wordplay, but flexible resources for interaction, evaluation, and self-positioning in digital discourse.